2018
DOI: 10.1155/2018/8989252
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Diabetes Mellitus Has No Major Influence on the Platelet Transcriptome

Abstract: Background Diabetes mellitus (DM) has been associated with increased platelet reactivity as well as increased levels of platelet RNAs in plasma. Here, we sought to evaluate whether the platelet transcriptome is altered in the presence of uncontrolled DM. Methods Next-generation sequencing (NGS) was performed on platelet RNA for 5 patients with uncontrolled DM (HbA1c 9.0%) and 5 control patients (HbA1c 5.5%) with otherwise similar clinical characteristics. RNA was isolated from leucocyte-depleted platelet-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In the literature, available data on miRNA are extremely various in terms of number and abundance of transcripts. 66,67,69,79,81 However, the most abundant miRNAs in platelets (e.g., miR-223, let7 family) correlate with our results.…”
Section: Qpcr Validationsupporting
confidence: 56%
See 2 more Smart Citations
“…In the literature, available data on miRNA are extremely various in terms of number and abundance of transcripts. 66,67,69,79,81 However, the most abundant miRNAs in platelets (e.g., miR-223, let7 family) correlate with our results.…”
Section: Qpcr Validationsupporting
confidence: 56%
“…Platelet transcriptome analyses published so far were performed collecting platelets directly from PRP. 66,67,79 This approach allows to collect billions of platelet to acquire enough genetic material but does not allow to isolate subgroups of interest. With this study, we isolated platelets from PRP by flow cytometry sorting with both positive (CD41 marker and platelet size) and negative (DNA staining) selection and we isolated RPs from peripheral blood using the state of the art staining with TO.…”
Section: Qpcr Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…A nested case-control study found significantly decreased hsa-miR-483-5p levels in the plasma of individuals with prediabetes which indicated its potential utility as a diagnostic predictor/circulating biomarker of β-cell function [45]. Significant downregulation of hsa-miR-539-5p was previously detected in the circulation of individuals with uncontrolled diabetes [46] while another study discovered its implications on both diabetes and the heart [47]. Down-regulation of both hsa-miR-1260a [48,49] and hsa--miR-4454 [49] in the circulation of individuals with T2D was also previously reported.…”
Section: Discussionmentioning
confidence: 92%
“…While results from RNA-sequencing in platelets from septic patients have been reported recently [ 11 ], this is to our knowledge the first study to simultaneously analyse levels of immature platelets in sepsis. Also, by magnetic bead-based leukocyte depletion, we obtained highly purified RNA for RNA-sequencing as previously described [ 28 ]. For the first time, we introduced the use of unique molecular identifiers to eliminate PCR amplification biases which may be relevant in a transcriptome with reduced complexity as it is observed in platelets [ 10 ].…”
Section: Discussionmentioning
confidence: 99%